Sympathetic Ophthalmia in Paediatric Post-Surgical Repair, A Case Report: Poster Presentation - Case Report - Resident - Muhammad Akbar Wicaksana; Irawati Irfani; Mayasari Wahyu Kuntorini; Sesy Caesarya; Feti Karfiati; Amiruddin, Primawita O. (Majalah Oftalmologi Indonesia, 2023)
Introduction : Sympathetic Ophthalmia (SO) is a rare and devastating complication of ocular trauma. Incidence reached 0.26% among cohort in paediatric open globe injury. We present a case report of pediatric Sympathetic Ophthalmia. Case Illustration : An 8-year-old boy is present in an outpatient clinic with a history of corneal lacerating injury on LE 1 month ago and had surgical repair 7 days after the injury. The patient complained of redness and blurry vision in both eyes. VA RE 0.5 and LE 0.05. RE revealed ciliary injection, flare/cell (f/s) +2/+2, and vitreous cell +1. LE revealed ciliary injection, corneal scars, f/s +2/+2, and vitreous cell +2 (Fig. 1). Fundus and OCT revealed macular oedema with exudative retinal detachment RE and bilateral optic nerve head swelling (Fig. 2). Patient was diagnosed with sympathetic ophthalmia and treated with prednisolone acetate 8x per day for RLE with high-dose oral steroid methylprednisolone 1 mg/kg body weight (32 mg). One week after treatment, clinical findings were improved, and the steroid was tapered. After 2 months f/s, macular oedema, exudative retinal detachment and optic nerve head swelling were resolved with VA RE 1.0 and LE 0.4. Discussion : Although the etiology of SO is currently unknown, it is believed that hypersensitivity following trauma to the fellow eye may be the trigger. The severity of SO's clinical presentation might range from mild to severe. Conclusion : Sympathetic ophthalmia is a serious complication that rarely occurs after trauma, especially in the pediatric population. Prompt treatment of oral and topical corticosteroids may lower the inflammatory response.